Utilization of ICT in Higher Education for Islamic Education Lecturers to Innovate - Rohman, Abdul; Tafsir, Ahmad; Yunus, Badruzaman (Lembaga Yasin AlSys, 2023)
Taking a theoretical approach, this paper explores the concept of educational innovation within Higher Education and the use of Information and Communication Technology (ICT) as a fundamental tool for achieving it. It aims to demonstrate how universities are now producers of knowledge operating within a new cultural and paradigmatic shift, whereby ICT has facilitated a continuous process of transformation and improvement. Additionally, mobile phones and other devices have become a common feature in the classroom, and can play a vital role in the learning process, however, it falls on teachers to determine how to best utilize them. The challenge of innovation is thus presented to educators. The importance of technological innovation has become a pressing issue in the digital age, with a consensus among the scientific community that educational innovation is inextricably linked to digital technologies.